IMPLEMENTASI INTEGRASI TEKNOLOGI DAN PEMBELAJARAN KONTEKSTUAL DALAM PEMBELAJARAN MENYIMAK BAHASA INGGRIS - Agustin, Helen; Sari, Dian Shinta; Astuti, Desi Sri (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
The rapid development of digital technology has transformed English language teaching, particularly listening instruction. Although various digital technologies have been integrated into classroom practices, the implementation of technology integration and contextual learning to promote students’ participation and classroom interaction in listening instruction requires further investigation. Therefore, this study aimed to describe the implementation of technology integration and contextual learning in English listening instruction. This study employed a descriptive qualitative research design. The research was conducted at a private senior high school in Pontianak involving one English teacher and 17 Grade XI students. Five students were purposively selected for semi-structured interviews. Data were collected through classroom observations, semi-structured interviews, and document analysis. The credibility of the findings was enhanced through data triangulation by comparing information obtained from multiple data sources. The data were analyzed using Braun and Clarke’s thematic analysis. The findings revealed that technology integration was implemented through the use of YouTube, Quizizz, audio recordings, smartphones, and other digital media during listening instruction. Contextual learning was reflected in authentic listening activities related to students’ daily experiences, encouraging active participation through classroom discussions, responses to teachers’ questions, completion of listening tasks, and peer collaboration. However, several challenges were identified, including unstable internet connections, limited technological facilities, and difficulties in understanding native-speaker pronunciation. The study concludes that integrating technology with contextual learning creates a more interactive, meaningful, and engaging listening learning environment while providing practical insights for English teachers in designing technology-supported listening instruction.